Bangladesh: The impact of COVID-19 and food system responses - COVID-19 Hub (International Food Policy Research Institute, 2021)
While Bangladesh has had reactionary responses to the newer waves of COVID-19, it is projected that the country could face severe consequences if the Delta variant detected in May 2021 spreads. Since the beginning of the health crisis, CGIAR and partners have worked to support a food systems response to the pandemic through informing national policies and improving food security